2004
DOI: 10.1023/b:agen.0000037329.45326.a8
|View full text |Cite
|
Sign up to set email alerts
|

Different Mechanisms Lead to the Angiogenic Process Induced by Three Adenocarcinoma Cell Lines

Abstract: Neoangiogenesis is essential for tumor and metastasis growth, but this complex process does not follow the same activation pathway, at least in tumor cell lines originated from different murine mammary adenocarcinomas. LMM3 cells were the most potent to stimulate new blood vessel formation. This response was significantly reduced by preincubating cells with indomethacin and NS-398, non-selective cyclooxygenase (COX) and COX-2 selective inhibitors, respectively. COX-1 and COX-2 isoenzymes were both highly expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…The function of ARG2 is not fully understood, but high levels of ARG2 have been described in tumors and cell lines (27,28). ARG2 was recently found overexpressed in cell lines derived from spontaneous murine mammary tumor and pulmonary metastases, and the authors suggested that ARG2 play a major role in tumor angiogenesis (29). These findings and the fact the ARG2 was found among the up-regulated tumor-related genes identified in a mice model that spontaneously develop FTC through progression of hyperplasia, capsular and vascular invasion, anaplasia, and eventually metastasis to distant organs (30) suggest that ARG2 may play a role in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The function of ARG2 is not fully understood, but high levels of ARG2 have been described in tumors and cell lines (27,28). ARG2 was recently found overexpressed in cell lines derived from spontaneous murine mammary tumor and pulmonary metastases, and the authors suggested that ARG2 play a major role in tumor angiogenesis (29). These findings and the fact the ARG2 was found among the up-regulated tumor-related genes identified in a mice model that spontaneously develop FTC through progression of hyperplasia, capsular and vascular invasion, anaplasia, and eventually metastasis to distant organs (30) suggest that ARG2 may play a role in carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report that NSAIDs seem to act directly on tumor cells with only minor effects on surrounding endothelial cells [26,27], while others put forward direct and main effects on the angiogenic process itself [28], similarly as seen in normal wound healing [29À32]. Also, various tumor cell lines seem to exert different effects on unanimous experimental conditions [33]. and in vivo, but host cells do also contribute to high circulating serum levels of PGE2 in mice with large tumor burden [14].…”
Section: Discussionmentioning
confidence: 99%
“…PGE 2 can induce and mediate expression of some oncogenes [25,26], display a strong immunosuppressive effect [27], and it is an important factor for angiogenesis [28,29], growth [7 9], and metastasizing [30] of tumors. On the other hand, some oncogenes, chemical carcinogens, promot ers, and various factors essential for carcinogenesis are inducers of COX and, as a consequence, the biosynthesis of PGE 2 [2,3,31].…”
Section: Discussionmentioning
confidence: 99%